WARTOŚCI LUDZI BEZDOMNYCH W RZECZYWISTOŚCI GLOBALNEJ - Motow, Irena (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Мотов Ирена. Ценности бездомных людей в глобальной действительности. Целью пред- принятого исследования есть существующая иерархия ценностей у бездомных, проживающих в Доме Брата Альберта. Исследования были проведены среди 100 подопечных приюта. Применялась нами шкала ценностей Шелеровских (SWS) переработанная Петром Бжозовским. С целью исследования иерархии ценностей бездомных лиц, респонденты получили письма, заключающие указанную шкалу ценностей. Заданием исследуемых лиц было ознакомление со списком ценностей, приведенных в порядке алфавит-ном, находящихся в полученном письме. После ознакомления с ними и выяснения, насколько важна для каждого из них данная ценность, исследователи предложили респондентам осуществить оценку ценнос-тей в письме, применяя для этой цели точечный масштаб. На полученном масштабе ценностей, неважное должно было оценить оценкой «ноль», зато ценности наиважнейшие получали 100 пунктов. Результаты опроса указывают, что в исследуемой группе 100 бездомных мужчин, проживающих в приюте, самыми существенными оказались ценности витальные. Ценности гедонистские, вопреки господствующим стереотипам, для бездомных имеют значение, хотя и не доминируют. Группа ценностей священных и связанных с утверждением истины размещены были рядом. Самую низкую ступеньку в иерархии ценностей занимают ценности из группы эстетичных. Особого внимания заслуживает факт, что Бог как ценность занимает самое высокое место в числе всех ценностей. Motow Irena. Values of homeless people are in global reality. The investigations of the values among individuals and social groups involve the deepest human dilemmas. This might cause that, despite the importance of this problem, there is little information concerning the state of the scientific research on the system of values among the homeless. The results presented in the paper are part of a more comprehensive survey on the hierarchy of values in the homeless. They concern the inhabitants of the Przytulisko Św. Brata Alberta (the St. Albert Shelter) in Częstochowa, Poland. The aim of the study was to define a hierarchy of values among the homeless who live in St. Albert’s shelters. The survey was carried out among 100 wards from the St. Albert Shelter. A Scheller’s Value Scale (Skala Wartości Schelerowskich, SWS) developed by Piotr Brzozowski was employed in the study. The respondents were asked to read the list of alphabetically ordered values in a questionnaire. After familiarizing with the questionnaire and thinking about the values which are important in their lives, the respondents were asked for assessment of the values listed, on a point scale. On this scale, the least important (unimportant) values scored 0, whereas the highest values (very important) scored 100 points. The results of the study showed that the most important values in the group of 100 homeless men living in the St. Albert’s Shelter were vital values. Contrary to the popular belief, the hedonistic values are important, but not dominant, among the group of the homeless. The group of sacred values and the values of truth took similar positions. The lowest level in the hierarchy of values was taken by the values from the group of aesthetical values. These values have been clearly defined by the homeless as the least important. It is remarkable that the value of God obtained the highest number of points among all the values in individual groups. Keywords: homelessness, hierarchy of values, vital values, sacred values.